2006
DOI: 10.3354/dao073063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on emergence, survival and infectivity of cercariae of the marine trematode Renicola roscovita (Digenea: Renicolidae)

Abstract: Marine bivalves harbour a diversity of trematode parasites affecting population and community dynamics of their hosts. Although ecologically and economically important, factors influencing transmission between first (snail) and second (bivalve) intermediate hosts have rarely been studied in marine systems. In laboratory experiments, the effect of temperature (10, 15, 20, 25 degrees C) was investigated on (1) emergence from snails, (2) survival outside hosts and (3) infectivity in second intermediate hosts of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…Contrary to other studies, in which infectivity positively correlated with increasing temperature [52], [53], the temperature treatment had no effect on the infectivity of C. lingua . Infection patterns were consistent across treatments and not influenced by the heat wave, which indicates that local adaptation between genotypes was more important than first order temperature effects on the parasite.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to other studies, in which infectivity positively correlated with increasing temperature [52], [53], the temperature treatment had no effect on the infectivity of C. lingua . Infection patterns were consistent across treatments and not influenced by the heat wave, which indicates that local adaptation between genotypes was more important than first order temperature effects on the parasite.…”
Section: Discussioncontrasting
confidence: 99%
“…there should be a high encounter rate. However, the maximum recovery rate was only around 35% (the differences in recovery rates in controls result from the strong temperature dependence of infection processes (Thieltges and Rick 2006)). Observational studies have indicated that host individuals may manage to reject approaching cercariae and even remove cercariae attempting to penetrate the foot Wegeberg et al 1999).…”
Section: Filtration Capacity In Mussel Units Recovery Relative To Conmentioning
confidence: 98%
“…The following regions were sampled: West-Netherlands (locations 1 and 2), East-Netherlands (locations 3 and 4), South-Germany (locations 5 and 6) and North-Germany (locations and 8). All beds were sampled in autumn 2012 (Online Resource 1) as this period is well suited for documenting infection levels of macroparasites (summer is the main period of production of trematodes (Thieltges and Rick 2006;Poulin 2006) and parasitic copepods (Grainger 1951) and of the settlement of P. ciliata larvae (Harms and Anger 1983).…”
Section: Sampling On Hierarchical Scalesmentioning
confidence: 99%